Surface Roughening Strategy for Highly Efficient Bifunctional Electrocatalyst: Combination of Atomic Layer Deposition and Anion Exchange Reaction. Issue 2 (30th December 2021) - Seenivasan, Selvaraj; Jung, Hyeonjung; Han, Jeong Woo; Kim, Do‐Heyoung
Abstract: Electrocatalytic water splitting, which is an interface‐dominated process, can be significantly accelerated by increasing the number of front‐line surface active sites ( N A ) of the electrocatalyst. In this study, a unique method is used for increasing the N A by converting the smooth ultrathin atomic‐layer‐deposited nanoshells of the electrocatalysts into nano‐roughened active shell layers using a controlled anion‐exchange reaction (AER). The coarse thin nanoshells present abundant surface active sites, which are generated owing to the inherent unit‐cell volume mismatch induced during the AER. Consequently, the nano‐roughened electrodes accelerate the sluggish water reaction kinetics and lower the overpotentials required for the hydrogen and oxygen evolution reactions. In addition, the electronic modulation induced by the nanoshell layer at the core–nanoshell interface amplifies the local electron density, as confirmed using electrochemical analysis data and density functional theory calculations. Because of the integrity of the composite electrodes during water‐splitting half‐cell reactions, their durability for industrial seawater electrolysis is evaluated. The results indicate that their electrochemical activity does not change significantly after 10 days of continuous overall water splitting. Abstract : Engineering electrochemical interfaces through in situ nano‐roughening using an anion‐exchange reaction increased the density of active sites and conferred excellent mass activity to the fabricated electrocatalysts. Electrocatalysts with nano‐roughened nanoshells outperformed conventional bulk core–shell electrocatalysts in an industrial seawater electrolyzer operated at a voltage of 1.57 V to deliver 100 mA cm −2 current density for more than 10 d without deterioration.